2021
DOI: 10.1186/s13287-021-02346-1
|View full text |Cite
|
Sign up to set email alerts
|

hERG-deficient human embryonic stem cell-derived cardiomyocytes for modelling QT prolongation

Abstract: Background Long-QT syndrome type 2 (LQT2) is a common malignant hereditary arrhythmia. Due to the lack of suitable animal and human models, the pathogenesis of LQT2 caused by human ether-a-go-go-related gene (hERG) deficiency is still unclear. In this study, we generated an hERG-deficient human cardiomyocyte (CM) model that simulates ‘human homozygous hERG mutations’ to explore the underlying impact of hERG dysfunction and the genotype–phenotype relationship of hERG deficiency. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…MEA recording in cardiomyocytes was performed as described previously ( 23 ). In brief, 2 × 10 4 cells were plated on CytoView MEA plates (Axion Biosystems, USA) pre-coated with 5% matrigel, followed by treatment with CYP at different concentrations (0 and 500 μmoL/L).…”
Section: Methodsmentioning
confidence: 99%
“…MEA recording in cardiomyocytes was performed as described previously ( 23 ). In brief, 2 × 10 4 cells were plated on CytoView MEA plates (Axion Biosystems, USA) pre-coated with 5% matrigel, followed by treatment with CYP at different concentrations (0 and 500 μmoL/L).…”
Section: Methodsmentioning
confidence: 99%
“…Itzhaki et al revealed that LQTS2 disease models show a significant prolongation of the APD due to a reduction in I Kr and evaluated the effects of some pharmacological agents on the disease phenotype ( Itzhaki et al, 2011 ). Chang et al (2021) used CRISPR/Cas9 editing to generate a KCNH2-KO hiPSC-CM model and showed that the model exhibited QT prolongation, irregular rhythm, and sensitivity to ion channel blockers such as L-type Ca channel blockers. Bellin et al (2013) demonstrated that correction of the KCNH2 mutation normalized the I Kr current conducted by the hERG channel and APD.…”
Section: Patient-specific Ipsc-cms As Disease Modelsmentioning
confidence: 99%
“…Both long-QT syndrome and short-QT syndrome are fatal inherited arrhythmogenic syndromes, which can cause apopsychia and death. A human ether-a-go-go-related gene-deficient CM model [ 6 ] with a pathogenic mutation, or mutation-corrected hiPSC-CMs [ 86 ], was established separately using CRISPR/Cas9, providing clues for malignant hereditary arrhythmia [ 6 ]. Moreover, the underlying molecular mechanism of congenital hepatic fibrosis (CHF) remains unclear.…”
Section: Applications Of Gene Editing In Pscs and Their Organoidsmentioning
confidence: 99%
“…Gene editing is broadly applied in disease modeling [ 6 ], exploring disease mechanisms [ 7 ] and disease targeting treatments [ 8 ]. Jennifer Doudna and Emmanuelle Charpentier, who pioneered gene-editing technology, were awarded the 2020 Nobel Prize in Chemistry, driving an unprecedented boom in the field [ 9 ].…”
Section: Introductionmentioning
confidence: 99%